Productivity and operational cost of mechanized weed control in young stands of Acacia mangium in the northern of Costa Rica - Guevara-Bonilla, Mario (2012)
Two mechanical weed control operations were assesed in young Acacia mangium stands located in the northern part of Costa Rica. Through a series of time and movement observations the productivity, efficiency and costs of both operations were determined. The two operations presented efficiency values higher than 55%. The productivity of the agricultural tractor was higher (4,98ha/day) than the obtained with trimmers (1,15 ha/day). Total cost per hectare was $13 for the agricultural tractor and $52 for trimmer.